ANALISIS MANAJEMEN SUMBER DAYA INSANI PADA BANK PEMBIAYAAN RAKYAT SYARIAH - Linda Sari; Ridan Muhtadi; Mansur Mansur (Faculty of Islamic Economics and Business, 2020)
Introduction: This study will analyze the human resource management at PT. BPRS Sarana Prima Mandiri Pamekasan in terms of recruitment and selection, training and employee development as well as employee performance appraisals. Methods: The research methodology used by researchers is descriptive qualitative which will explain the events and circumstances in detail and perfectly with data collection techniques using observation, interviews and documentation. Results: This research is deemed necessary considering that the development of Islamic banking in Indonesia is relatively fast but is still not balanced with adequate human resources, both in quality and quantity. and one of the company's mission is supported by human resources. Conclusion and suggestion: This study indicates that human resource management at PT. BPRS Sarana Prima Mandiri (SPM) Pamekasan in terms of recruitment and selection is in accordance with sharia theory. Likewise, the work appraisal process is in accordance with the Islamic concept. However, in the training and development process, according to researchers, there is still a lack of material balance, namely between the material of Tauhid (Akhlak), Shari'ah, and Muamalah which is conveyed to employees when the training is carried out. Keywords: Islamic banking, recruitment and selection, training and development, employee performance appraisal.